Membangun Spiritualitas Pelayanan Kaum Muda - Hendrikus Tekwan; Antonius Denny Firmanto (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
The purpose of this writing is to see how far young people serve others in their lives, especially those who need young people's help. The purpose of this writing also wants to actualize how important it is for young people to serve one another. The method used in this paper is descriptive analysis to see the characteristics of each questionnaire filled out by young people. In addition, the writer wants to know what fears exist in young people when they want to serve. The data obtained through a questionnaire were 100 respondents, namely young people aged 15-25 years in Mahakam Hulu Regency. The results of testing the hypothesis prove that the feeling of caring for young people in serving others is still reasonably good. Through this writing, the author wants to make it relevant to the life of Jesus and His disciples in terms of helping the people in Jerusalem and its surroundings.